PENINGKATAN DISOLUSI CELECOXIB MELALUI PEMBENTUKAN DISPERSI PADAT DENGAN HPMC-PEG 6000 - Eva Kartalina; Danang Novianto Wibowo (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2021)
Celecoxib (CLX) is a drug that has low solubility and high permeability and belongs to BCS class II. The low solubility of CLX results in the bioavailability of CLX being only 40%, so it is necessary to increase the dissolution using a solid dispersion (DP) technique. This study aims to determine the dissolution profile of CLX in DP with a carrier combination of HPMC and PEG 6000. DP CLX were prepared by solvent evaporation method using drug-HPMC-PEG 6000 ratios were (1:1:1), (1:1:2) and (1:2:1). Pure CLX, physical mixture (CF) at the same ratio and DP were tested for dissolution in tribasic sodium phosphate 0.04 M (pH 12) and 1% sodium lauryl sulfate (SLS). The data from the dissolution test in the form of Q45 and DE60 values were analyzed statistically using non-parametric test. Overall Q45 DP CLX value > 75% and significantly different from pure CLX and CF. DE60 CLX value in DP ratio (1:1:1) 59.13±0.44%; ratio (1:1:2) 60.77±0.09%; ratio (1:2:1) 60.47±0.42%. Solid dispersion with a combination of HPMC polymer and PEG 6000 was able to increase the dissolution of celecoxib compared to the physical mixture and pure celecoxib.